Metodología gerencial para facility management ambientalmente sostenible en Bogotá D. C. (2021)
Some companies constantly perform corrective maintenance solutions and perform in poor lease conditions environment and underutilized spaces that disregard ergonomics. This article describes how to develop a management methodology for the administration of locative maintenance projects by applying facility management with an environmental sustainability approach in corporate buildings in Bogota, Colombia. A diagnosis of the most common facilities management services was carried out and different management approaches and environmental standards were analyzed in order to provide environmental sustainability and efficient use to companies by preserving their properties and valuing them over time.